2015
DOI: 10.5846/stxb201310192524
|View full text |Cite
|
Sign up to set email alerts
|

The succession characteristics and its driving mechanism of plant community in karst region, southwest China

Abstract: Vegetation restoration is the key step of desertification prevention and ecological rehabilitation in the karst region in Southwest China. A sound understanding of the vegetation composition, species diversity, and structural variation with succession is of great significance for vegetation protection and rehabilitation. However, until now, a systematic synthesis of information was not available for this region. In this study, we thoroughly collected the relevant data from the literature and unpublished data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Interestingly, most of the species showing smaller size, shallower water uptake, lower leaf δ 13 C/WUEi and extensive canopy defoliation or mortality during drought are typical pioneer, early‐successional species ( V. negundo , A. trewioides , P. fortuneana , M. repandus ) that are dominant in degraded karst areas. Conversely, the majority of the species of larger size using deeper water sources and exhibiting higher leaf δ 13 C/WUEi, moderate drought‐induced defoliation and drought survival ( S. rotundifolium , S. euosma , P. tonkinense) typically become dominant in late‐successional karst vegetation stages (Wen et al ., 2015). It thus appears that the late‐successional species of mature karst forests have undergone high selective pressure for deep rooting and heavy reliance on more temporally stable water sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, most of the species showing smaller size, shallower water uptake, lower leaf δ 13 C/WUEi and extensive canopy defoliation or mortality during drought are typical pioneer, early‐successional species ( V. negundo , A. trewioides , P. fortuneana , M. repandus ) that are dominant in degraded karst areas. Conversely, the majority of the species of larger size using deeper water sources and exhibiting higher leaf δ 13 C/WUEi, moderate drought‐induced defoliation and drought survival ( S. rotundifolium , S. euosma , P. tonkinense) typically become dominant in late‐successional karst vegetation stages (Wen et al ., 2015). It thus appears that the late‐successional species of mature karst forests have undergone high selective pressure for deep rooting and heavy reliance on more temporally stable water sources.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven woody plant species of contrasting life form and leaf habit were selected for assessing the impacts of experimental rainfall exclusion (Table 1). Among them, V. negundo , A. trewioides , Pyracantha fortuneana , Mallotus repandus , Schefflera octophylla and R. sinica are pioneer species typical of early‐successional vegetation stages, whereas the remaining five species ( C. biondii , Diospyros dumetorum , S. rotundifolium , S. euosma , P. tonkinense ) usually appear during middle‐ or late‐ successional stages during vegetation recovery from disturbance (Wen et al ., 2015). Three to five individuals of each target species were present in the rainfall exclusion plot and all of them were used for the ecophysiological measurements explained below.…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously, however, coexisting species experience strong interspecific competition because of their similar resource requirements (Castagneri et al, 2008). In subtropical steep rocky mountain habitats (Wen et al, 2015), shrublands are dominated by S. chinensis , which is the closest relative of C. oblonga (Figure 6). In the studied community, however, the S. chinensis population is declining and gradually being replaced by C. oblonga (Figures 3 and 4), supporting the conclusion that “the naturalization of alien species severely harms closely related native species, leading to their local extinction” (Li, Cadotte, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, however, coexisting species experience strong interspecific competition because of their similar resource requirements (Castagneri et al, 2008). In subtropical steep rocky mountain habitats (Wen et al, 2015), shrublands are dominated by S. chinensis, which is the closest relative of C. oblonga (Figure 6).…”
Section: Potential Drivers Of Cydonia Oblonga Naturalizationmentioning
confidence: 99%
“…In order to satisfy the greater resource demand, larger aboveground species need to develop a relatively large root system (Westoby and Wright, 2006). Previous studies in karst regions showed that during the early stages of restoration in with infertile soil conditions, plants have not yet developed large root systems, only small shrubs can be supported to survive and thrive (Wen et al, 2015;Zhang et al, 2015), which has also been shown in non-karst studies (A. G. T, 1916;Glenn-Lewin et al, 1993;Jiang et al, 2018). In terms of leaf phenology, compared with the evergreen species, deciduous species require more resources during the rainy season because of their concentrated growth (Hasselquist et al, 2010;Nie et al, 2014b;Wang and Moore, 2014;Delzon, 2015;Salazar-Tortosa et al, 2018).…”
mentioning
confidence: 99%